ERRORS ANALYSIS IN SHORT BIOGRAPHY TEXT WRITTEN BY THE 11th GRADE STUDENTS OF A VOCATIONAL HIGH SCHOOL IN SINGARAJA - Suwastini, N.K.A; Yukti, W.G.S. (Universitas Pendidikan Ganesha, 2017)
This study was a descriptive qualitative study aimed at analysing types of error and sources of error in the short biography text writings in English language teaching (ELT) context. The subject of this study was 11th Grade of Accounting Department Students of a Vocational High School in Singaraja in the academic year 2015/2016. The instruments in the study were researcher, tabulation table, and interview guide. The textual analysis design was used in this study to gather the data. The students’ errors were analysed according to surface strategy taxonomy by Dulay et al. (1982). This study revealed that misformation was the most frequent errors occurred in the students’ writings, followed by omission, addition, and misordering. Furthermore, the sources of error were identified according to four sources of error by Brown (2007). This study found that interlingual transfer was the main sources of students’ errors, followed by context of learning, interlingual transfer, and communication strategy. Related to these findings, the present study suggested that teachers pay more serious attention to students’ errors by comparing the students’ first language system and the target language system in order to avoid errors.